1840 Outbreaks, Outcries, Outliers: Who Responds to Measles Elimination Goals in the European Region with Innovative Behaviour Change Tools. (October 2012) - Butler, R; Likhite, N
Abstract : Background and Aims Measles outbreaks: in the World Health Organisation (WHO)'s European Region continue to threaten the achievement of the 2015 elimination goal. Over 37, 000 measles cases were reported in 2011 alone. Failure to vaccinate is the principal obstacle to optimal national and sub-national immunity. In a context where loss of public confidence in vaccination is often cited, experts deplore the presence of vaccination outliers and outcries of anti-vaccine lobbyists. Generating demand for vaccination is a pivotal strategy for elimination. However, the traditional "one-size fits all" approach to immunisation communications no longer meets current needs. WHO's aim is to offer a toolkit for Member States to design effective targeted vaccination demand generation campaigns. Methods: A review of literature on vaccination behaviours shows that reasons for not vaccinating are multiple and complex. Drawing on international best practices in health behaviour change communications and social marketing, WHO Regional Office for Europe has developed an adaptable, innovative conceptual framework and tools to help countries understand and identify environmental opportunity, supportive ability and personal motivation determinants of vaccination behaviours, target susceptible populations and tailor evidence-based programmes to increase uptake of vaccination. Results and conclusions: Building Member States' capacity to profile and tailor responses to susceptible populations will result in higher vaccination coverage and accelerate progress towards eliminating measles in the European Region. The approach and tools will be piloted in two Member States in 2012. Further, they will be implemented by WHO in partnership with Ministries of Health from 2013 on.